Self-repairing material containing dynamic hindered thiourea bond as well as preparation method and application of self-repairing material
By introducing dynamically hindered thiourea bonds into the polydimethylsiloxane matrix, the problem of poor insulation and self-repairing performance of traditional repairable silicone rubber is solved, and the material is bestowed without reducing its insulation performance.
Patent Information
- Application Number
- CN202411974375.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-15
AI Technical Summary
The existing repairable silicone rubber has poor insulation and self-repairing properties and is not suitable for insulating materials.
The material is self-healed by the formation of dynamically hindered thiourea bonds by using raw materials such as polydimethylsiloxane, diisothiocyanate compounds and anhydrous piperazine.
Without sacrificing insulation performance, the material is repaired, so that it not only has good insulation and mechanical properties, but also has excellent self-repair performance, and is suitable for power equipment such as cable sheaths or accessories.
Smart Images

Figure CN119823343A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of polymer materials, and in particular to a self-repairing material containing a dynamically hindered thiourea bond, and a preparation method and application thereof. Background Art
[0002] Insulating materials based on silicone rubber are widely used in power equipment. However, the modulus, mechanical strength and wear resistance of silicone rubber itself are relatively poor. During the production, transportation and installation of power equipment using silicone rubber insulation materials, it is easy to suffer mechanical damage such as scratches and wear under external influences. These damages will cause changes in its surface morphology, resulting in various morphological defects such as scratches, burrs, and holes, further leading to uneven electric field distribution, thereby affecting its material life and insulation reliability. Material surface damage is one of the important factors that cause the operating life of power equipment in actual applications to be significantly lower than the ideal life.
[0003] At present, repair or self-healing materials can fill and bond material damage defects under certain external effects, repair damage and extend the service life of materials. Since the beginning of this century, more than 10 materials and systems with repair capabilities have been reported, including epoxy resin, silicone rubber, and polyurethane. Among them, polymer materials with repair capabilities can be divided into two types according to the repair mechanism. Among them, external aid repairable materials are introduced into traditional polymer materials by introducing microcapsules, microspheres or microtube bundles. When the material is partially damaged. The microcapsules, microspheres or microtube bundles near the area release their internal repair agents due to damage. These repair agents repair the damaged area under external catalysts or light and heat stimulation conditions. Another intrinsic repairable material is to construct a cross-linked network based on a dynamic chemical structure at the polymer structure scale. This cross-linked network is different from the traditional three-dimensional cross-linked network. It can undergo reversible topological rearrangement under appropriate external stimulation conditions to achieve self-repair of the material.
[0004] In the existing technology, repairable silicone rubber has made significant progress. However, the existing research system focuses more on the recovery of mechanical properties, and there are few reports on the research of insulation performance and repair mechanism. In addition, many dynamic chemical structures in repairable silicone rubber, such as dynamic ionic bonds, dynamic metal coordination bonds, intermolecular interactions, and dynamic covalent structural systems that require the introduction of metal ion catalysts, may cause the insulation performance to deteriorate, so they are not suitable for insulating materials.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The main purpose of the present invention is to provide a self-healing material containing a dynamically hindered thiourea bond and a preparation method and application thereof, so as to solve the problem that the conventional repairable silicone rubber in the prior art has poor insulation and self-healing properties and is not suitable for use as an insulating material.
[0007] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a self-healing material containing a dynamically hindered thiourea bond is provided, wherein the raw materials of the self-healing material include polydimethylsiloxane, a diisothiocyanate compound, anhydrous piperazine and an optional amine cross-linking agent; and the molar ratio of the four is (3-4):6:2:(0-0.7); wherein both ends of the polydimethylsiloxane are capped with aminoalkyl groups.
[0008] Furthermore, the diisocyanate compound includes at least one of p-phenylene diisocyanate, o-phenylene diisocyanate, m-phenylene diisocyanate, toluene-2,4-diisocyanate, and toluene-2,6-diisocyanate.
[0009] Further, the amine cross-linking agent includes at least one of tris(2-aminoethyl)amine and 1,3,5-tri(amino)benzene.
[0010] Furthermore, the number average molecular weight of the polydimethylsiloxane is 1,000-10,000.
[0011] Furthermore, the aminoalkyl group is aminopropyl group.
[0012] According to another aspect of the present invention, a method for preparing a self-healing material containing a dynamically hindered thiourea bond provided in the first aspect is provided, comprising the following steps: step S1, mixing polydimethylsiloxane, a diisothiocyanate compound, anhydrous piperazine and an optional amine cross-linking agent with an organic solvent to obtain a raw material mixture; step S2, removing the organic solvent from the raw material mixture, and then hot pressing to form a film to obtain a self-healing material containing a dynamically hindered thiourea bond.
[0013] Furthermore, the organic solvent includes at least one of tetrahydrofuran, ethyl acetate and dichloromethane.
[0014] Furthermore, the organic solvent is removed by drying.
[0015] Furthermore, the drying temperature is 60 to 90° C., and the drying time is 7 to 12 hours.
[0016] Furthermore, the temperature of hot pressing film forming is 100-150° C., the time of hot pressing film forming is 5-20 min, and the pressure of hot pressing film forming is 5-15 MPa.
[0017] According to the third aspect of the present invention, provided is the use of the self-healing material containing dynamically hindered thiourea bonds provided by the first aspect or the self-healing material containing dynamically hindered thiourea bonds obtained by the preparation method provided by the second aspect in power equipment.
[0018] Using the technical solution of the present invention, the present application provides a self-healing material, which is based on polydimethylsiloxane and reacts the isothiocyanate group in the diisothiocyanate monomer with the amino group (amino group in the polydimethylsiloxane double-capped with aminoalkyl, and the secondary amine of anhydrous piperazine) to quickly and efficiently generate a thiourea bond without a catalyst. Among them, the diisothiocyanate monomer and anhydrous piperazine form a dynamically hindered thiourea bond. Due to the steric hindrance effect of the secondary amine in anhydrous piperazine, the bond energy of the thiourea bond is weakened, further promoting the dissociation-association of the thiourea bond. The dynamic dissociation-association of the thiourea bond is used to cause a recombination reaction on the damaged surface, further promoting the self-repair of the material.
[0019] Polydimethylsiloxane has good insulation properties. This application uses a self-healing material formed by a specific molar ratio of polydimethylsiloxane, diisocyanate monomer, and anhydrous piperazine to introduce dynamically hindered thiourea bonds into polymer materials, giving them repair capabilities without sacrificing their insulation properties, so that the self-healing material not only has good insulation properties and mechanical properties but also has excellent self-healing properties. That is, the material can recover from damage by reshaping after damage, and the self-healed material can still maintain excellent insulation and mechanical properties. The self-healing material is suitable for power equipment such as cable sheaths or accessories. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0021] Figure 1 Schematic diagrams of the self-healing material containing dynamically hindered thiourea bonds prepared in Example 1 before and after repair are shown. DETAILED DESCRIPTION
[0022] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0023] As analyzed in the background technology of this application, there is a problem in the prior art that traditional repairable silicone rubber has poor insulation and self-healing properties and is not suitable for insulating materials. In order to solve this problem, this application provides a self-healing material containing a dynamically hindered thiourea bond, and a preparation method and application thereof.
[0024] In a typical embodiment of the present application, a self-healing material containing a dynamically hindered thiourea bond is provided, wherein the raw materials of the self-healing material include polydimethylsiloxane, a diisothiocyanate compound, anhydrous piperazine and an optional amine cross-linking agent; and the molar ratio of the four is (3-4):6:2:(0-0.7); wherein both ends of the polydimethylsiloxane are capped with aminoalkyl groups.
[0025] In the present application, in the polydimethylsiloxane terminated with aminoalkyl groups at both ends, the alkyl end of the aminoalkyl group is connected to the siloxane end of the polydimethylsiloxane.
[0026] The self-healing material is based on polydimethylsiloxane, and the isothiocyanate group in the diisocyanate monomer reacts with the amino group (amino group in polydimethylsiloxane double-terminated with aminoalkyl and secondary amine of anhydrous piperazine) to quickly and efficiently generate a thiourea bond without the need for a catalyst. The diisocyanate monomer and anhydrous piperazine form a dynamically hindered thiourea bond. Due to the steric hindrance effect of the secondary amine in anhydrous piperazine, the bond energy of the thiourea bond is weakened, further promoting the dissociation-association of the thiourea bond. The dynamic dissociation-association of the thiourea bond is used to cause a recombination reaction on the damaged surface, further promoting the self-healing of the material.
[0027] Polydimethylsiloxane has good insulation properties. This application uses a self-healing material formed by a specific molar ratio of polydimethylsiloxane, diisocyanate monomer, and anhydrous piperazine to introduce dynamically hindered thiourea bonds into polymer materials, giving them repair capabilities without sacrificing their insulation properties, so that the self-healing material not only has good insulation properties and mechanical properties but also has excellent self-healing properties. That is, the material can recover from damage by reshaping after damage, and the self-healed material can still maintain excellent insulation and mechanical properties. The self-healing material is suitable for power equipment such as cable sheaths or accessories.
[0028] When an amine crosslinker is added to the self-healing material, the amino groups in the amine crosslinker bond with the isothiocyanate groups in the diisothiocyanate monomer, which can crosslink the linear structure into a network structure, and affect the insulation, mechanical and self-healing properties of the self-healing material through the degree of crosslinking. When the molar proportion of the amine crosslinker in the raw material increases, the degree of crosslinking increases, and the crosslinked structure hinders the flow of current, improves the insulation properties of the material, and improves the insulation properties of the self-healing material; at the same time, the increase in the degree of crosslinking restricts the movement of the polymer chain, and the mechanical properties of the self-healing material are also improved; but the crosslinked network restricts the movement of the chain segments, resulting in a lower probability of group collision, which leads to a reduction in the self-healing ability.
[0029] When the amine crosslinker is excessive, the degree of crosslinking is further increased, which will lead to a decrease in tensile strength. This is because the crosslinking point is a dynamic bond, which is easy to break under the action of external force and cannot fully play the role of enhancing the tensile strength of the material; at the same time, the probability of group collision is very low, resulting in almost no self-repair effect. Therefore, the present application adds a specific molar ratio of amine crosslinkers to enable the self-repairing material to maintain both excellent insulation properties and excellent self-repairing properties.
[0030] Self-healing materials containing dynamically hindered thiourea bonds can self-repair damage, and the self-healing process is mainly based on the chemical properties of the thiourea bond and the special structure of the dynamically hindered thiourea bond. Due to the steric hindrance effect of the secondary amine in anhydrous piperazine, the dynamically hindered thiourea bond in the self-healing material can weaken the bond energy of the thiourea bond, thereby further promoting the dissociation-association of the thiourea bond in the self-healing process, so that a recombination reaction occurs between broken particles or damaged surfaces, restoring the continuity and insulation properties of the material. In actual operation, after the material is broken or damaged, the broken particles or damaged surfaces are spliced together and fixed, and the thiourea bonds are dissociated by simple means (such as heating treatment). Once the thiourea bonds at the broken or damaged site are dissociated, they are recombined with the adjacent amino or isothiocyanate groups to form new thiourea bonds, thereby achieving self-repair of the material and restoring (or approaching) its original performance. During the repair process, the negative impact of the dynamic bond repair mechanism on the insulation performance is avoided, ensuring that the repaired material can still maintain its excellent insulation properties.
[0031] The synthesis principle of the self-healing material containing a dynamically hindered thiourea bond is shown below. When no amine cross-linking agent is added, a linear structure is presented, and when an amine cross-linking agent is added, a network structure is presented. The self-healing material with a linear structure has a higher repair efficiency than the self-healing material with a network structure because the molecular chain thermal motion is more flexible.
[0032]
[0033] Note: In the synthesis principle diagram of the above self-healing material containing dynamically hindered thiourea bonds, n is an integer between 1 and 1,000,000.
[0034] In order to further improve the repair efficiency of the self-healing material, the heating treatment temperature during the repair process is preferably 80°C to 100°C, and the heating treatment time is 40 to 72 hours.
[0035] Typically but not limiting, the temperature of the heating treatment is 80°C, 85°C, 90°C, 95°C, 100°C or a range consisting of any two values; the time of the heating treatment is 40h, 44h, 48h, 50h, 55h, 60h, 65h, 70h, 72h or a range consisting of any two values.
[0036] Typically but not restrictively, the molar ratio of polydimethylsiloxane, diisocyanate monomer, anhydrous piperazine and optional amine cross-linking agent in the raw materials of the self-healing material provided in the present application is 3:6:2:0, 3:6:2:0.7, 3:6:2:0.667, 4:6:2:0, 4:6:2:0.667, 4:6:2:0 or a range consisting of any two numerical values.
[0037] In order to further improve the insulation performance of the self-healing material, the molar ratio of polydimethylsiloxane to amine crosslinker is preferably 3:6:2:0.7, 3:6:2:0.667 or 4:6:2:0.
[0038] In some embodiments, the diisocyanate monomer includes any one or more of p-phenylene diisocyanate, o-phenylene diisocyanate, m-phenylene diisocyanate, toluene-2,4-diisocyanate, and toluene-2,6-diisocyanate to further efficiently generate thiourea bonds and further improve the mechanical properties of the self-healing material. In order to further improve the mechanical properties and self-healing properties of the self-healing material, it is more preferred that the diisocyanate monomer is p-phenylene diisocyanate.
[0039] In some embodiments, the amine crosslinking agent includes any one or more of tris(2-aminoethyl)amine and 1,3,5-tri(amino)benzene to further promote the formation of a network structure inside the self-healing material, thereby further improving the insulation performance of the self-healing material. In order to further improve the insulation performance of the self-healing material, the amine crosslinking agent is more preferably tris(2-aminoethyl)amine.
[0040] In some embodiments, the number average molecular weight of polydimethylsiloxane is 1000-10000. Polydimethylsiloxane with a number average molecular weight within this range has high fluidity, which is conducive to the dissociation and recombination of dynamically hindered thiourea bonds and accelerates the damage repair process; in addition, the number average molecular weight can also affect the length and chain spacing of the molecular chain, thereby affecting the migration of charges in the material. When the number average molecular weight of polydimethylsiloxane is 1000-10000, it helps to prevent the free flow of charges and further improve the insulation performance.
[0041] Typically but not limiting, the number average molecular weight of the polydimethylsiloxane is 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000 or a range consisting of any two of these numbers.
[0042] In the present application, both ends of the polydimethylsiloxane may be capped with aminoalkyl groups, including but not limited to aminopropyl groups, preferably aminopropyl groups.
[0043] In some embodiments, the total molar amount of the amino group of anhydrous piperazine, the amino group of polydimethylsiloxane, and the optional amino group of tri(2-aminoethyl)amine is the same as the molar amount of the isothiocyanate group of p-phenylene diisothiocyanate, so that the isothiocyanate group reacts completely with the amino group, ensuring maximum formation of thiourea bonds, enhancing the stability of the structure, and further improving the self-healing efficiency and insulation properties of the material.
[0044] In a second typical embodiment of the present application, a method for preparing a self-healing material containing a dynamically hindered thiourea bond is provided, and the preparation method comprises the following steps: step S1, mixing polydimethylsiloxane, a diisothiocyanate compound, anhydrous piperazine and an optional amine cross-linking agent with an organic solvent to obtain a raw material mixture; step S2, removing the organic solvent from the raw material mixture, and then hot pressing it into a film to obtain a self-healing material containing a dynamically hindered thiourea bond.
[0045] The preparation method provided by the present application is simple, the preparation process is green and environmentally friendly, and it is easy to realize industrial production. And the self-healing material is based on polydimethylsiloxane, and the isothiocyanate group in the diisothiocyanate monomer reacts with the amino group (amino group in polydimethylsiloxane double-capped with aminoalkyl, and secondary amine of anhydrous piperazine) to quickly and efficiently generate a thiourea bond without the need for a catalyst. Among them, the diisothiocyanate monomer and anhydrous piperazine construct a dynamically hindered thiourea bond. Due to the steric hindrance effect of the secondary amine in anhydrous piperazine, the bond energy of the thiourea bond is weakened, further promoting the dissociation-association of the thiourea bond. The dynamic dissociation-association of the thiourea bond is used to cause a recombination reaction on the damaged surface, further promoting the self-repair of the material.
[0046] Polydimethylsiloxane has good insulation properties. This application uses a self-healing material formed by a specific molar ratio of polydimethylsiloxane, diisocyanate monomer, and anhydrous piperazine to introduce dynamically hindered thiourea bonds into polymer materials, giving them repair capabilities without sacrificing their insulation properties, so that the self-healing material not only has good insulation properties and mechanical properties but also has excellent self-healing properties. That is, the material can recover from damage by reshaping after damage, and the self-healed material can still maintain excellent insulation and mechanical properties. The self-healing material is suitable for power equipment such as cable sheaths or accessories.
[0047] In order to further promote the dissolution of the raw materials, especially the dissolution of anhydrous piperazine, thereby ensuring that the reaction raw materials can be fully dispersed, and further improve the reaction rate and the uniformity of the product, the organic solvent preferably includes any one or more of tetrahydrofuran, ethyl acetate, and dichloromethane.
[0048] In step S2, the organic solvent in the mixture is removed to solidify the product for subsequent processing, testing and use. At the same time, the removal of the organic solvent also ensures the purity and performance of the self-healing material and avoids the organic solvent from adversely affecting the insulation and repair properties of the self-healing material. In order to quickly remove the organic solvent, it is preferred that the organic solvent is removed by drying.
[0049] In order to further improve the removal rate of the organic solvent, the drying temperature is preferably 60 to 90° C. and the drying time is 7 to 12 hours.
[0050] Typically, but not limiting, the drying temperature is 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or a range consisting of any two values. The drying time is 7h, 8h, 9h, 10h, 11h, 12h or a range consisting of any two values.
[0051] In step S2, the organic solvent in the mixture is removed and then hot-pressed, which can promote the reaction between the groups, cross-link the raw materials to form a stable cross-linked network, and at the same time improve the density and stability of the self-healing material, ensuring that it has good insulation and repair properties.
[0052] In order to further promote the reaction and cross-linking between the groups, the preferred temperature for hot pressing is 100-150°C, the time for hot pressing is 5-20 minutes, and the pressure for hot pressing is 5-15 MPa. When the pressure of hot pressing is too small or the temperature is too low, the hot pressing will be uneven. When the pressure of hot pressing is too large or the temperature is too high, the self-healing material will be oxidized.
[0053] Typically but not limitatively, the temperature of hot pressing molding is 100°C, 110°C, 120°C, 130°C, 140°C, 150°C or a range consisting of any two values; the time of hot pressing molding is 5 min, 8 min, 10 min, 12 min, 15 min, 18 min, 20 min or a range consisting of any two values; the pressure of hot pressing film forming is 5 MPa, 8 MPa, 10 MPa, 12 MPa, 15 MPa or a range consisting of any two values.
[0054] In a third typical embodiment of the present application, there is provided an application of the self-healing material containing dynamically hindered thiourea bonds provided in the first typical embodiment or the self-healing material containing dynamically hindered thiourea bonds obtained by the preparation method provided in the second typical embodiment in power equipment, specifically, a cable sheath or an accessory.
[0055] The beneficial effects of the present application will be further illustrated below in combination with embodiments and comparative examples.
[0056] Example 1
[0057] The present embodiment provides a method for preparing a self-healing material containing a dynamically hindered thiourea bond, comprising the following steps: (1) mixing polydimethylsiloxane terminated with aminopropyl groups at both ends, anhydrous piperazine and tetrahydrofuran, and placing the mixture in a magnetic stirrer, stirring the mixture at 70° C. and 800 rpm for 12 h to obtain a mixture.
[0058] (2) After fully mixing p-phenylene diisocyanate and tetrahydrofuran, add the mixture dropwise to the mixture of step (1), place the mixture in a magnetic stirrer, and stir at 70° C. and 800 rpm for 6 h to obtain a raw material mixed solution.
[0059] (3) The raw material mixture was placed in an oven at 70°C for 10 h and poured into a stainless steel mold. The stainless steel mold was then placed in a flat vulcanizer and preheated at 100°C for 10 min. The mold was then hot-pressed at a pressure of 10 MPa for 10 min. After the hot-pressing was completed, the mixture was cooled for 10 min and demolded to obtain a self-healing material containing dynamically hindered thiourea bonds.
[0060] In the raw materials of this embodiment, the molar ratio of polydimethylsiloxane terminated with aminopropyl groups at both ends, p-phenylene diisothiocyanate, and anhydrous piperazine is 4:6:2; the number average molecular weight of polydimethylsiloxane is 3000.
[0061] Example 2
[0062] This embodiment provides a method for preparing a self-healing material containing a dynamically hindered thiourea bond, comprising the following steps:
[0063] (1) Polydimethylsiloxane capped at both ends with aminopropyl groups, anhydrous piperazine, tri(2-aminoethyl)amine and tetrahydrofuran were mixed and placed in a magnetic stirrer, and stirred at 70° C. and 800 rpm for 12 h to obtain a mixture.
[0064] (2) After fully mixing p-phenylene diisocyanate and tetrahydrofuran, add the mixture dropwise to the mixture of step (1), then place in a magnetic stirrer and stir at 70° C. and 800 rpm for 6 h to obtain a raw material mixed solution.
[0065] (3) The raw material mixture was placed in an oven and dried at 70°C for 10 h, poured into a stainless steel mold, and then placed in a flat vulcanizer. The mold was preheated at 100°C for 10 min, and then hot-pressed at a pressure of 10 MPa for 10 min. After hot pressing, the mold was cooled for 10 min and demolded to obtain a self-healing material containing dynamically hindered thiourea bonds.
[0066] In the raw materials of this embodiment, the molar ratio of polydimethylsiloxane terminated with aminopropyl groups at both ends, p-phenylene diisothiocyanate, anhydrous piperazine, and tri(2-aminoethyl)amine is 3:6:2:0.667; the number average molecular weight of polydimethylsiloxane is 3000.
[0067] Example 3
[0068] The difference from Example 1 is that the number average molecular weight of the polydimethylsiloxane in this example is 1000.
[0069] Example 4
[0070] The difference from Example 1 is that the number average molecular weight of the polydimethylsiloxane in this example is 10,000.
[0071] Example 5
[0072] The difference from Example 1 is that the number average molecular weight of the polydimethylsiloxane in this example is 500.
[0073] Example 6
[0074] The difference from Example 1 is that the number average molecular weight of the polydimethylsiloxane in this example is 15,000.
[0075] Example 7
[0076] The difference from Example 1 is that the diisocyanate compound in this example is toluene-2,4-diisothiocyanate.
[0077] Example 8
[0078] The difference from Example 2 is that the amine cross-linking agent in this example is 1.3.5-tri(amino)benzene.
[0079] Comparative Example 1
[0080] The difference from Example 1 is that the raw materials of this comparative example do not contain anhydrous piperazine, and the molar ratio of polydimethylsiloxane terminated with aminopropyl groups at both ends to p-phenylene diisothiocyanate is 6:6.
[0081] Comparative Example 2
[0082] The difference from Example 1 is that the molar ratio of polydimethylsiloxane terminated with aminopropyl groups at both ends, p-phenylene diisothiocyanate, and anhydrous piperazine in the raw materials of this comparative example is 5:6:1.
[0083] Comparative Example 3
[0084] The difference from Example 1 is that the molar ratio of polydimethylsiloxane terminated with aminopropyl groups at both ends, p-phenylene diisothiocyanate, and anhydrous piperazine in the raw materials of this comparative example is 2:6:4.
[0085] Comparative Example 4
[0086] The difference from Example 2 is that the raw materials of this comparative example do not contain anhydrous piperazine, and the molar ratio of polydimethylsiloxane terminated with aminopropyl groups at both ends, p-phenylene diisothiocyanate, and tris(2-aminoethyl)amine is 4:6:1.333.
[0087] Comparative Example 5
[0088] The difference from Example 2 is that the molar ratio of polydimethylsiloxane terminated with aminopropyl groups at both ends, p-phenylene diisothiocyanate, anhydrous piperazine, and tris(2-aminoethyl)amine in the raw materials of this comparative example is 3.74:6:1:0.84.
[0089] Comparative Example 6
[0090] The difference from Example 2 is that the molar ratio of polydimethylsiloxane terminated with aminopropyl groups at both ends, p-phenylene diisothiocyanate, anhydrous piperazine, and tris(2-aminoethyl)amine in the raw materials of this comparative example is 1.5:6:4:0.334.
[0091] Comparative Example 7
[0092] The difference from Example 2 is that the content of each component in the raw material is adjusted in this comparative example so that the molar ratio of polydimethylsiloxane terminated with aminopropyl groups at both ends, p-phenylene diisothiocyanate, anhydrous piperazine, and tri(2-aminoethyl)amine is 2:6:2:1.333.
[0093] Test Example 1
[0094] The self-healing material samples provided in this embodiment and the comparative example were cut with a clean blade, the sample cuts were stitched together and clamped between glass sheets, and the glass sheets were fixed with a binder clip. The fixed samples were placed in a 90° C. oven for repair for 48 hours and then taken out to obtain self-healed samples.
[0095] The schematic diagram of the self-healing material containing dynamically hindered thiourea bonds in Example 1 before and after repair is as follows: Figure 1 As shown, from Figure 1 It can be seen that the incision almost completely disappeared after 48 hours of heat treatment, proving that it produced a repair effect.
[0096] The original tensile strength and original breakdown field strength of the self-healing material samples provided in the embodiments and comparative examples, as well as the tensile strength and breakdown field strength after self-healing of the self-healed samples were tested respectively, and the tensile strength self-healing rate and the breakdown field strength self-healing rate were calculated. The results are shown in Table 1.
[0097] 1. The sample was cut into a dumbbell shape with a length of 35 mm, a narrow part width of 2 mm, and a sample thickness of 1 mm. The tensile strength was tested in accordance with the national standard GBT 528-2009.
[0098] 2. Under the condition that the sample thickness is about 0.3 mm, the voltage is increased at a rate of 10 kV / s until breakdown occurs, and the breakdown field strength is obtained.
[0099] Tensile strength self-repair rate = (tensile strength after self-repair / original tensile strength) × 100%
[0100] Breakdown field strength self-repair rate = (breakdown field strength after self-repair / original breakdown field strength) × 100%
[0101] Table 1
[0102]
[0103]
[0104] Note: "--" means that the sample is very likely to break down during the measurement process, and the breakdown field strength after self-repair cannot be measured.
[0105] From the results of Example 1, Example 2, and Comparative Example 7, it can be seen that when the raw materials of the self-healing material include aminopropyl dicapped polydimethylsiloxane, diisothiocyanate compounds, anhydrous piperazine, and an optional amine cross-linking agent, and the molar ratio of the four is (3-4):6:2:(0-0.7), it not only has a higher original tensile strength and original breakdown field strength, but also has a higher tensile strength self-repair rate and breakdown field strength self-repair rate, indicating that the self-healing material provided by the present application has excellent insulation properties, mechanical properties, and self-healing properties. And when an appropriate amine cross-linking agent is added to Example 2, the original tensile strength and the original breakdown field strength are slightly higher, and the tensile strength self-repair rate and the breakdown field strength self-repair rate are slightly lower, indicating that the degree of cross-linking increases, hindering the flow of current and the movement of polymer chains, and promoting the improvement of the insulation and mechanical properties of the self-healing material, but at the same time, the probability of group collision is reduced, resulting in a slight decrease in the self-healing performance. However, when an excess of amine crosslinker is added in Comparative Example 7, although the original breakdown field strength is significantly increased, the probability of group collision is significantly reduced, resulting in almost no self-repair effect. Therefore, the self-repair rate of tensile strength is significantly reduced, and breakdown is very likely to occur during the measurement process.
[0106] It can be seen from the experimental results of Example 1, Example 3 to Example 6 that when the number average molecular weight of polydimethylsiloxane is in the range of 1000-10000, the self-healing material has a higher original tensile strength, original breakdown field strength, and a higher tensile strength self-repair rate and breakdown field strength self-repair rate, indicating that the self-healing material has excellent insulation properties, mechanical properties and self-healing properties. When the number average molecular weight of polydimethylsiloxane is too small, the degree of crosslinking increases. Although it hinders the flow of current and the movement of polymer chains, the original breakdown field strength and original tensile strength of the self-healing material are improved, but it also leads to a decrease in the probability of group collision, resulting in a significant decrease in the tensile strength self-repair rate and the breakdown field strength self-repair rate. On the contrary, when the number average molecular weight of polydimethylsiloxane is too large, although the self-healing performance is improved, the insulation performance and mechanical properties are significantly reduced.
[0107] It can be seen from the experimental results of Examples 7-8 that when the diisocyanate compound is toluene-2,4-diisocyanate or the amine cross-linking agent is 1,3,5-tri(amino)benzene, the self-healing material also has excellent insulation properties, mechanical properties and self-healing properties.
[0108] It can be seen from the experimental results of Example 1, Comparative Examples 1-3 and Example 2, Comparative Examples 4-5 that when the self-healing material includes aminopropyl dicapped polydimethylsiloxane, diisothiocyanate compounds, anhydrous piperazine and an optional amine crosslinker, and the molar ratio of the four is (3-4):6:2:(0-0.7), the self-healing material has excellent insulation properties, mechanical properties and self-healing properties. When the raw material does not contain anhydrous piperazine or the content of anhydrous piperazine is too little, the self-healing rate of tensile strength and the self-healing rate of breakdown field strength are significantly reduced. This is because the number of dynamically hindered thiourea bonds is reduced, resulting in a significant reduction in self-healing performance. When the content of anhydrous piperazine in the raw material is too much, although the self-healing performance is improved, the original mechanical strength and original insulation performance are reduced.
[0109] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0110] The self-healing material is based on polydimethylsiloxane, and the isothiocyanate group in the diisocyanate monomer reacts with the amino group (amino group in polydimethylsiloxane double-terminated with aminoalkyl and secondary amine of anhydrous piperazine) to quickly and efficiently generate a thiourea bond without the need for a catalyst. The diisocyanate monomer and anhydrous piperazine form a dynamically hindered thiourea bond. Due to the steric hindrance effect of the secondary amine in anhydrous piperazine, the bond energy of the thiourea bond is weakened, further promoting the dissociation-association of the thiourea bond. The dynamic dissociation-association of the thiourea bond is used to cause a recombination reaction on the damaged surface, further promoting the self-healing of the material.
[0111] Polydimethylsiloxane has good insulation properties. This application uses a self-healing material formed by a specific molar ratio of polydimethylsiloxane, diisocyanate monomer, and anhydrous piperazine to introduce dynamically hindered thiourea bonds into polymer materials, giving them repair capabilities without sacrificing their insulation properties, so that the self-healing material not only has good insulation properties and mechanical properties but also has excellent self-healing properties. That is, the material can recover from damage by reshaping after damage, and the self-healed material can still maintain excellent insulation and mechanical properties. The self-healing material is suitable for power equipment such as cable sheaths or accessories.
[0112] When an amine crosslinker is added to the self-healing material, the amino groups in the amine crosslinker bond with the isothiocyanate groups in the diisothiocyanate monomer, which can crosslink the linear structure into a network structure, and affect the insulation, mechanical and self-healing properties of the self-healing material through the degree of crosslinking. When the molar proportion of the amine crosslinker in the raw material increases, the degree of crosslinking increases, and the crosslinked structure hinders the flow of current, improves the insulation properties of the material, and improves the insulation properties of the self-healing material; at the same time, the increase in the degree of crosslinking restricts the movement of the polymer chain, and the mechanical properties of the self-healing material are also improved; but the crosslinked network restricts the movement of the chain segments, resulting in a lower probability of group collision, which leads to a reduction in the self-healing ability.
[0113] When the amine crosslinker is excessive, the degree of crosslinking is further increased, which will lead to a decrease in tensile strength. This is because the crosslinking point is a dynamic bond, which is easy to break under the action of external force and cannot fully play the role of enhancing the tensile strength of the material; at the same time, the probability of group collision is very low, resulting in almost no self-repair effect. Therefore, the present application adds a specific molar ratio of amine crosslinkers to enable the self-repairing material to maintain both excellent insulation properties and excellent self-repairing properties.
[0114] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A self-healing material containing a dynamically hindered thiourea bond, characterized in that: The raw materials of the self-healing material include polydimethylsiloxane, diisothiocyanate compounds, anhydrous piperazine and an optional amine cross-linking agent; and the molar ratio of the four is (3-4):6:2:(0-0.7); wherein both ends of the polydimethylsiloxane are capped with aminoalkyl groups.
2. The self-healing material containing dynamically hindered thiourea bonds according to claim 1, characterized in that: The diisocyanate compound includes at least one of p-phenylene diisocyanate, o-phenylene diisocyanate, m-phenylene diisocyanate, toluene-2,4-diisocyanate and toluene-2,6-diisocyanate.
3. The self-healing material containing dynamically hindered thiourea bonds according to claim 1, characterized in that: The amine cross-linking agent includes at least one of tris(2-aminoethyl)amine and 1,3,5-tri(amino)benzene.
4. The self-healing material containing dynamically hindered thiourea bonds according to claim 1, characterized in that: The number average molecular weight of the polydimethylsiloxane is 1000-10000.
5. The self-healing material containing dynamically hindered thiourea bonds according to claim 1, characterized in that: The aminoalkyl group is aminopropyl.
6. A method for preparing a self-healing material containing a dynamically hindered thiourea bond according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: Step S1, mixing the polydimethylsiloxane, the diisothiocyanate compound, anhydrous piperazine and the optional amine cross-linking agent with an organic solvent to obtain a raw material mixed solution; Step S2, removing the organic solvent in the raw material mixture, and then hot pressing to form a film to obtain a self-healing material containing dynamically hindered thiourea bonds.
7. The preparation method according to claim 6, characterized in that: The organic solvent includes at least one of tetrahydrofuran, ethyl acetate and dichloromethane.
8. The preparation method according to claim 6, characterized in that: The method of removing the organic solvent is drying; Preferably, the drying temperature is 60-90° C., and the drying time is 7-12 hours.
9. The preparation method according to claim 6, characterized in that: The temperature of the hot pressing film forming is 100-150° C., the time of the hot pressing film forming is 5-20 min, and the pressure of the hot pressing film forming is 5-15 MPa.
10. Use of the self-healing material containing a dynamically hindered thiourea bond according to any one of claims 1 to 5 or the self-healing material containing a dynamically hindered thiourea bond obtained by the preparation method according to any one of claims 6 to 9 in power equipment.
Citation Information
Cited By
Intelligent elastomer for photocuring 3D printing and preparation method thereof
CN122356388A